Laporan Kasus: Stage Closure untuk Gastroskisis - Tubagus Odih R Wahid; Ari Alvaren; Lofina Mutia Dewi; Putri Sari; Widya Cahya Purnama (Fakultas Kedokteran Universitas Riau, 2020)
Gastroschisis is a congenital defect of the anterior abdominal wall which is to the right of the umbilicus, gastric, small intestine and colon can be found outside the abdominal cavity. The incidence is 1: 2.500-10.000 births. The incidence of Gastroschisis in the world has increased in the last 30 years. In Indonesia, the incidence of Gastroschisis is not yet clear. The diagnosis is relatively easy by inspection and it is found that the contents of the abdomen are exposed outside the abdominal cavity. We reported a case of a baby patient aged six days when he was sent to Bagan Siapi Api Hospital and then performed the first stage operation, namely the installation of the bogota bag procedure, followed by gradual squist sac ligase treatment, after 18 days of treatment or at 37 days of age, devinitive surgery was performed close the abdominal wall defect